'It's all there.': Entanglements of teacher preparation and induction. Issue 2 (27th May 2021) - Wallace, Maria F.G.; Rust, Julie; Jolly, Elisabeth
ABSTRACT: Teacher preparation and induction are two notable hallmarks of teacher-becoming commonly presumed to be detached from one another, forcing teacher candidates to transition linearly from one phase to another. Our study challenges this notion through one newly developed teacher residency programme where participating teacher residents are positioned to navigate the simultaneous entanglement of concepts. Using critical posthumanist theories alongside poetic inquiry, this study works at the speculative middles of teacher preparation and induction. We examine a small slice of data from a larger study to zoom into individual interviews with undergraduate teacher residents to explore the question: What does the entanglement of teacher preparation and induction reveal about becoming a teacher? Through our analysis we found that becoming a teacher is (a) fraught with multidimensional relations of obligation; (b) disrupts linear conceptions of space and time; and (c) functions as a co-constitutive property to the production of practices. Furthermore, these findings illuminate ways a critical posthumanist lens might render new questions thinkable for teacher education practice and research. Examining how one residency programme works at the 'speculative middles' of multiple concepts produces an abundance of reverberating implications for expanding a non-linear engagement with research on teacher becoming.